Smart Iron Board / Muhammad Hisyamuddin Hamzah - Hamzah, Muhammad Hisyamuddin (2020)
This report is meant as an insight over the product development for the innovative product that are to be designed, constructed and marketed for a particular market and industries. EZ Sdn.Bhd is a new company established in May 2020 with a vision to be people number one iron board furniture manufacturer in Malaysia. Our mission is to provide the iron board that promotes eco-friendly function where people can use the multifunction iron board that provided mirror and small storage in limited spaces. My product has innovated the existences of iron board into additional features and design modifications that could satisfy the Malaysian society. Hence, my company aims to find ways in order to solve the problems and to provide the people with a better version of the furniture that can answer to modern day problems. In this report, I will provide the insight on the phases of the development of my product. Among the phases includes the research and development of my intended product in regard of the innovation I targeted on, followed by the design procedure of my intended product for the market. In order to ensure the viability of the product, be it both the short term and the long term. For this purpose, multiple testing of my product will be conducted thoroughly, beginning with the concept testing of the product involved. This process will be followed by the construction of a workable prototype of our product in order to test its ergonomic, its functionality as well to identify any unforeseen limitation of our product for further improvement, in there is any. My product will also be tested on the market in order to gain insight over the opinions and reception of our targeted customer group in order to ensure that it is able to compete on the market upon the completion of my marketable product.